Media Internalized Pressure and Restrained Eating Behavior in College Students: The Multiple Mediating Effects of Body Esteem and Social Physique Anxiety - Fu, Tiantian; Wang, Jun; Xu, Shanshan; Yu, Jinrong; Sun, Guoxiao (Frontiers in Psychology, 2022)
Background Restrained eating behavior has become the norm in college students' lives, and considering the harm it causes to college students, it is necessary to explore the factors associated with it. The aim of this study was to explore the association between media internalized pressure, body esteem, social physique anxiety, and restrained eating behavior. Methods The participants in this study were 1,032 Chinese college students (439 males and 593 females) and had a mean age of 20.22 years (SD = 1.277). They completed the Sociocultural Attitudes Toward Appearance Questionnaire-3, Body Esteem Scale (BES), Social Physique Anxiety Scale (SPAS), and Dutch Eating Behavior Questionnaire (DEBQ). Results The results showed that media internalized pressure was significantly and positively associated with college students' restrained eating behavior, that body esteem and social physique anxiety played a mediating role between media internalized pressure and restrained eating behavior, respectively, and that body esteem and social physique anxiety can also play a chained mediating role. Conclusion This study reveals the relationship between media internalized pressure and restrained eating behavior, and the important role played by body esteem and social physique anxiety. Future interventions targeting restrained eating should focus on the aspects of body esteem and social physique anxiety.